Low temperature thermal and electrical transport properties of ZrZn2 in high magnetic field - Zou, Yang; Rothfuß, Daniel Simon; Fleischmann, Andreas; Enss, Christian (Journal of physics. Conference Series, 2012)
The low temperature electrical and thermal transport properties of the itinerant ferromagnet ZrZn 2 were investigated in order to explore the nature of the Fermi-liquid breakdown in this material. We have implemented electrical and thermal conductivity measurements down to temperatures of 100 mK and in high magnetic field. In zero field and above 2 K the electrical and effective thermal resistivities take a T 5/3 and T -linear form, respectively. These are the signatures of the marginal Fermi-liquid, predicted to occur close to a ferromagnetic quantum critical point by spin fluctuation theory. In contrast, we find that below 2 K and in external magnetic field the electrical resistivity assumes a quadratic temperature dependence, consistent with a return to conventional Fermi-liquid behaviour.
Die Zahl 2 ist im Titel tiefgestellt
Gesehen am 27.03.2018